Termite infestation on timber structure of residential building / Suhana Iryani Noor Azmy - Noor Azmy, Suhana Iryani (Faculty of Architecture, Planning and Surveying, 2014)
Termite is an insect that eats wood and damaged houses, walls, columns, floorings, furniture and books. Termites are capable of efficiently digesting cellulose, the major component in wood. This singular ability enables termites to play important ecological roles and makes them major structural pests worldwide. Termite can eat timber without been notice. They can hide in the building without any sign that can find. But the occupant usually take easy regarding the termite matter, they not aware about what damages that can be done by a termite colonies. They survive by eating the wood in the building, if the foundation of the building is timber material, its can make the building collapse. A few method was conducted to achieve the objective, site analysis and site observation was carried out to determine the factor that influence the termite infestation and to identify the presence of termite infestation in timber structure. The questionnaire was distributed to 30 homeowner to investigate the level of awareness, of homeowner towards termite infestation .-in timber building structure. As additional input, interview session with termite's specialist, En. Iswade Md Adib from URC GLOBAL CARE SDN. BHD. There are few factor can consume to termite infestation such as temperature and humidity of building, timber moisture content, the surrounding or adjacent area of the building. The homeowner is lack of knowledge or information about termite infestation. Their level of awareness regarding the termite infestation is quite low. Even though they have been experience this problem.